(untitled) (Bioresearch Communications, 2024)
Salinity stress adversely affects rice (Oryza sativa L.) growth, development and overall productivity. Multiple strategies have been implemented to enhance the resilience of rice plants, enabling them to grow better in saline environments. Use of biofertilizers, a sustainable alternative to chemical fertilizers, has gained significant attention in modern agriculture due to their potential to improve soil fertility, enhance crop productivity, and mitigate environmental concerns. Biofertilizers encompass a diverse group of microorganisms, including bacteria, fungi, and algae, which interact with plants through various mechanisms. These beneficial microbes have been reported to convert atmospheric nitrogen into plant-available forms and break down insoluble phosphates and zinc complexes in the soil. Additionally, they can also produce growth regulators, enhance nutrient availability, and protect plants against pathogens. In our previous study, a salt-tolerant endophytic fungus isolated from the halophytic wild rice, Oryza coarctata, was identified as Aspergillus welwitschiae Ocstreb1 by whole genome sequence analysis. During the in-vitro experiments, the endophyte showed several plant growth promoting activities such as, zinc and phosphate solubilization, siderophore, IAA, and ACC-deaminase production, nitrogen fixation, etc. in both normal and 900 mM salt stress. In this study, the endophyte was used to formulate a biofertilizer in combination with talcum powder to enhance the growth and yield of rice plants under salinity stress. This research investigated the effectiveness of the biofertilizer in four distinct salinity tanks under both non-saline and 6 dS/m saline conditions, each containing three different varieties of rice. Treatment of BRRI dhan28 (BD-28), BRRI dhan67 (BD-67) and BRRI dhan87 (BD-87) rice plants with the formulated biofertilizer significantly enhanced their yield in both non-saline and saline conditions. Among the three rice varieties, BD-28 showed the highest significant (p<0.05) yield increase, with 104.20% under normal conditions and 3080.56% under salt stress. BD-67 exhibited a 45.15% increase in normal conditions and 153.64% under salt stress (P<0.05). BD-87 showed a significant yield increase only under salt stress, at 293.63% (p<0.05). From the results of the study, it can be proposed that the formulated biofertilizer is a potential eco-friendly and cost-effective solution to improve cultivation and yield of rice in the highly saline coastal regions of Bangladesh. Bioresearch Commu. 10(2): 1474-1481, 2024 (July)